BALANCED SCORECARD: PENTINGNYA PERSPEKTIF PROSES BISNIS INTERNAL STUDI EMPIRIS DI PONPES - St. Dwiarso Utomo; Zaky Mahmuddah; Yulita Setiawanta (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2016)
The purpose of this research is to find an empirical evidence of implementation of internal business process perspective of Balanced Scorecard (BSC) in Assalaam Islamic Modern Boarding School Surakarta (AIMBS Surakarta). The research is case study. Qualitative research design is conducted using semi-structured interviews with 21 members from different stakeholders. The research findings showed that internal business process perspective of BSC and attributes in strategy map of BSC have been implemented well in AIMBS Surakarta. Besides, the research also found supporting factor of implementation of internal business process perspective of BSC in AIMBS Surakarta, namely: strong commitment from top management to adjust the change dan to improve the service to the stakeholders. The limitation of the research is that the research findings can not be generalized because of case study. For future research, the researcher can add the numbers of research object so that the generalization of research findings can be gained. Theoretically, it will give clearer description about the implementation of internal business processperspective of BSC in Islamic boarding schools.